2020
DOI: 10.1155/2020/4272090
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Cu-Catalysed Si Nanowires as an Anode for Lithium-Ion Cells

Abstract: Silicon (Si) nanowires (NWs) grown on stainless-steel substrates by Cu-catalysed Chemical Vapour Deposition (CVD) have been prepared to be used as anodes in lithium-ion batteries. The use of NWs can overcome the problems related to the Si volume changes occurring during lithium alloying by reducing stress relaxation and preventing material fragmentation. Moreover, since the SiNWs are grown directly on the substrate, which also acts as a current collector, an excellent electrical contact is generated between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In subsequent cycles a good reversibility was observed even if the Coulombic efficiency did not exceed 95 %, suggesting the formation of an unstable SEI film and a continuous decomposition of the electrolyte on the silicon surface. [21] Considerable loads of active material (2-5 mg cm À 2 ) and, consequently, highcapacity densities was obtained using carbon paper as the substrate. It has been observed that, a very slow first cycle (C/ 40) helps the formation of a stable SEI on the silicon surface and improves the performance of the cells.…”
Section: Innovative Electrode Materials For Li-and Na-ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations
“…In subsequent cycles a good reversibility was observed even if the Coulombic efficiency did not exceed 95 %, suggesting the formation of an unstable SEI film and a continuous decomposition of the electrolyte on the silicon surface. [21] Considerable loads of active material (2-5 mg cm À 2 ) and, consequently, highcapacity densities was obtained using carbon paper as the substrate. It has been observed that, a very slow first cycle (C/ 40) helps the formation of a stable SEI on the silicon surface and improves the performance of the cells.…”
Section: Innovative Electrode Materials For Li-and Na-ion Batteriesmentioning
confidence: 99%
“…Silicon nanowires were grown on copper [21] or carbon paper [22] substrate and the influence of growth parameters (silane gas pressure, temperature, and deposition time) on the morphology and crystalline structure of the product was evaluated. The electrochemical characterization showed that a large irreversible capacity affected the electrode during the first cycle and, to a lesser extent, during the second cycle.…”
Section: Outcomes Of the Projectmentioning
confidence: 99%
See 1 more Smart Citation